AN EFFECT OF PRODUCT AND PRICE ON CUSTOMER SATISFACTION AT COFFEE TAKE AWAY COFFEE - Rizwanul Yakin Nasution; Nur Ainun (Sean Institute, 2023)
In the beginning, drinking coffee was a habit of Indonesian people since ancient time.The development of coffee business trends in Indonesia has been going quite rapidly in recent times.Because Indonesia is the country that produces the best coffee beans in the world. The growth of coffee shops in Indonesia has mushroomed in various big cities and even small towns have mushroomed coffee shops, although they still have different standards and markets. This study aims to determine the effect of product and price on customer satisfaction at Kedai Coffee Toffee Surabaya. The population in this study were consumers who visited the Take Away Coffee in Medan and the sample in this study was 60 respondents. Based on the results of data processing with SPSS version 25, it was found that all statement items from all variables were declared valid because r count > from r table and all variables were declared reliable because Cronbach Alpha > 0.7. The results of the normality test stated that the data in this study were normally distributed and declared valid. In the multicollinearity test, the tolerance value of all variables was found to be more than 0.10 and the VIF value was less than 10 so that it can be concluded that the research data did not experience multicollinearity between the independent variables. In the heteroscedasticity test, it can be seen that the points spread over the number 0 on the Y axis and do not form a clear pattern, so heteroscedasticity occurs in the regression model. Multiple linear regression is obtained by the regression model as follows Y = 1.384 + 0.169 X1 + 0.576 X2 . the result of the test for the determinant coefficient (R2) is 0.639, which means that product and price have a strong influence on customer satisfaction by 63.9%. In the t test it was found that product and price had a significant effect on customer satisfaction at Take Away Coffee.